Most large colorectal polyps missed by gastroenterology fellows at colonoscopy are sessile serrated lesions - Vemulapalli, Krishna C.; Lahr, Rachel E.; Rex, Douglas K. (Endoscopy International Open, 2022)
Background and study aims Data on adenoma and sessile serrated lesion (SSL) miss rates for gastroenterology fellows during colonoscopy are limited. We aimed to describe the miss rate of fellows based on a second examination by a colonoscopist with a high rate of detection.Patients and methods Second- and third-year gastroenterology fellows at a single, tertiary center performed initial examinations. A single experienced attending doctor then performed a complete examination of the colon. We recorded the size and pathology of all lesions found at both examinations and calculated the adenoma and SSL miss rates for fellows.Results Ten trainees performed 100 examinations. Miss rates for conventional adenomas and SSLs were 30.5 % and 85.7 %, respectively. Among pre-cancerous polyps ≥ 10 mm, 10 of 14 lesions missed were SSLs.Conclusions While conventional adenoma detection skills of gastroenterology fellows are acceptable, SSL detection is poor.